The pollination biology of Pseudostifftia kingii H.Rob. (Asteraceae), a rare endemic Brazilian species with uniflorous capitula - Hipólito de Sousa, Juliana (2013)
(The pollination biology of Pseudostifftia kingii H.Rob. (Asteraceae), a rare endemic Brazilian species with uniflorous capitula). P. kingii is a monotypic genus within the Asteraceae family that grows under extreme environmental conditions and possesses an unusual single-flowered capitulum. It is endemic to Chapada Diamantina, Bahia, Brazil, a region dominated by a mosaic of rocky, sandy flats and bogs in the upper elevational zone (above 900-1,000 m). To gain a better understanding of the pollination biology of P. kingii, we examined its floral development, floral rewards, reproductive strategies, and floral visitors. The flowers exhibit asynchronous diurnal anthesis with three distinct floral stages, each differing with regard to male-female maturation and nectar availability; these floral stages appear to influence the activity of the flower visitors. Although several floral characteristics of P. kingii suggest that it is an entomophilous species, observations revealed it as a generalist species for which hummingbirds and bees are the main floral visitors, differing slightly in the diurnal period of their visits. P. kingii can reproduce through xenogamy, geitonogamy, and what appears to be allogamy, but with different sizes of fruits (achenes) produced depending on the reproductive strategy employed. This study revealed some important features of pollination and floral biology within Asteraceae and provides clues for pollen dispersion in a harsh environment.